Diagnosis of Left Ventricular Hypertrophy in the Presence of Left Anterior Fascicular Block: A Reexamination of the 2009 AHA/ACCF/HRS Guidelines - Ravi, Sandeep (Ann Noninvasive Electrocardiol, 2013)
BACKGROUND: The 2009 “AHA/ACCF/HRS Recommendations for Standardization and Interpretation of the Electrocardiogram” state that left ventricular hypertrophy (LVH) criteria that include R‐wave amplitude in leads I and aVL are not likely reliable in the presence of left anterior fascicular block (LAFB). This statement was referenced to three relatively small studies. The present study reexamines the utility of selected electrocardiographic (ECG) criteria for LVH in the presence of LAFB. METHODS: We identified 185 ECG tracings with LAFB from patients in whom echocardiogram had been performed within 30 days of the ECG. These ECGs were evaluated for the presence of selected LVH criteria: (1) Sokolow index (R‐wave‐aVL > 11 mm); (2) Cornell criteria (R‐wave‐aVL + S‐wave‐V3 > 28 mm in men (>20 mm in women); (3) Gertsch criterion (S‐wave‐III + (R + S) maximal precordial >30 mm); and (4) Bozzi criterion (SV1 or SV2 + (RV6 + SV6) > 25 mm). The “gold standard” for LVH was left ventricular mass index on echocardiogram. RESULTS: Although the aVL‐based LVH criteria demonstrated lower sensitivity (45–68%) and a trend toward higher specificity (67–81%) compared to non‐aVL‐based criteria, the four studied criteria demonstrated similar diagnostic accuracy. CONCLUSIONS: In the presence of LAFB, the aVL‐based Sokolow index and Cornell criteria, which were excluded from 2009 multisociety ECG guidelines, identify LVH with similar diagnostic accuracy as the non‐aVL‐based criteria that were included. Moreover, they are easier to calculate and are included in some of the computer‐assisted ECG interpretation software presently in use. Their exclusion from the 2009 guidelines was unnecessary.